2008
DOI: 10.1111/j.1365-2230.2008.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Excising basal cell carcinomas: comparing the performance of general practitioners, hospital skin specialists and other hospital specialists

Abstract: GPs compare unfavourably with skin specialists in diagnosing and excising BCCs. The performance of nonspecialized GPs does not appear to differ markedly from that of GPwSI. There is considerable room to optimize current GP performance, particularly with lesions of the head and neck, and it may be that novel approaches to GP training are required to achieve this. Structured request forms may improve the quality of clinical information provided when skin biopsies are submitted for pathological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 15 publications
6
49
2
Order By: Relevance
“…Previous studies found similar proportions of complete BCC excisions; however, these studies lack a sample size calculation, subgroup analyses per tumor site and histological subtype, and logistic regressions [8][9][10][11]. Dermatologists probably excise BCC more often complete than GPs and plastic surgeons because dermatologists are specifically trained in BCC care during their 5 years of specialization, and dermatologists are more experienced in BCC care due to the high case load in their daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found similar proportions of complete BCC excisions; however, these studies lack a sample size calculation, subgroup analyses per tumor site and histological subtype, and logistic regressions [8][9][10][11]. Dermatologists probably excise BCC more often complete than GPs and plastic surgeons because dermatologists are specifically trained in BCC care during their 5 years of specialization, and dermatologists are more experienced in BCC care due to the high case load in their daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns have been echoed in research that found that GPs compare unfavourably with skin specialists in diagnosing and excising basal cell carcinomas (BCCs), the commonest malignancy excised in primary care; whereas non-specialised GPs perform no worse than GPs with a special interest (GPwSI). 2 However, the same authors found that GPs performed as well, if not better, than specialists in excising squamous cell carcinomas (SCC); whereas, again, practicebased GPs performed as well as GPwSIs. 3 Further research by the same authors showed that melanoma excisions by GPs appeared to be of similar quality to those undertaken by specialists; there was no difference demonstrated between frequent and infrequent GP surgeons.…”
Section: Introductionmentioning
confidence: 98%
“…Standards are usually not monitored except by audit of individual doctors, with training generally being informal 'peer to peer' learning, with occasional continuing medical education activities. 2,3 and other countries [4][5][6][7] have shown that skin specialists diagnose and excise skin cancers better than GPs. GPs may unnecessarily remove benign lesions or, because of cost barriers for some patients, refer minor lesions to hospital clinics, placing a high demand on these services.…”
Section: Background and Assessment Of Problemmentioning
confidence: 99%